2020
DOI: 10.3390/w12082142
|View full text |Cite
|
Sign up to set email alerts
|

Combining Water Quality Indices and Multivariate Modeling to Assess Surface Water Quality in the Northern Nile Delta, Egypt

Abstract: Assessing surface water quality for drinking use in developing countries is important since water quality is a fundamental aspect of surface water management. This study aims to improve surface water quality assessments and their controlling mechanisms using the drinking water quality index (DWQI) and four pollution indices (PIs), which are supported by multivariate statistical analyses, such as principal component analysis, partial least squares regression (PLSR), and stepwise multiple linear regression (SMLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 50 publications
2
30
3
Order By: Relevance
“…The correlation analysis between the two variables presents a perfect linear relationship [80]; therefore, the correlation metric with TDS and IWQ revealed that Ca 2+ was the most affected cation and alkalinity was the most affected anion. These results are in agreement with the water facies, which were presented by the Piper Diagram and reflected the effects of weathering and rock water interactions reported in the Gibbs Diagram [71]. In general, there were weak relationships between the trace elements and six WQIs of surface water.…”
Section: Correlation Coefficient Of the Relationship Between Wqis Witsupporting
confidence: 89%
See 3 more Smart Citations
“…The correlation analysis between the two variables presents a perfect linear relationship [80]; therefore, the correlation metric with TDS and IWQ revealed that Ca 2+ was the most affected cation and alkalinity was the most affected anion. These results are in agreement with the water facies, which were presented by the Piper Diagram and reflected the effects of weathering and rock water interactions reported in the Gibbs Diagram [71]. In general, there were weak relationships between the trace elements and six WQIs of surface water.…”
Section: Correlation Coefficient Of the Relationship Between Wqis Witsupporting
confidence: 89%
“…Furthermore, alkalinity values in the samples collected registered their highest from surface water, which may have been derived from atmospheric silicate weathering and carbonate dissolution [78]. According to the previous work of Gad et al [71], the water facies in this region are belongs to Ca 2+ -Mg 2+ -HCO 3 − and Ca 2+ -Mg 2+ -Cl − -SO 4 2− , which was affected by rock water interaction processes and weathering. The major ions are powerful tools for detecting solute sources; the wide ranges of the ions in the surface water samples indicate the effect of several recharging sources, e.g., surface canals, anthropogenic practise, drains and overuse of fertilizers and pesticides [17].…”
Section: Physicochemical Parameters and Water Faciesmentioning
confidence: 72%
See 2 more Smart Citations
“…Principal Component Analysis (PCA) leads to the detection of the main water parameters that influence water quality [20]. Gad et al [21] combined a drinking water quality index and four pollution indices, principal component analysis (PCA), partial least squares regression (PLSR), and stepwise multiple linear regression (SMLR) to evaluate the water quality for drinking purposes in the Nile Delta.…”
Section: Introductionmentioning
confidence: 99%